Dimensional stability of distances between teeth in complete dentures comparing microwave polymerization and conventional cycles - Wagner Araújo de Negreiros; Rafael Leonardo Xediek Consani; Marcelo Ferraz Mesquita (Universidade Estadual de Campinas, 2015)
Aim: This study investigated the tooth movement of complete dentures processed by microwave activation and conventional processing method in water bath. Methods: Twenty maxillary complete dentures were fabricated and randomly assigned to 4 groups (n=5): Group I: Classico conventional heat-curing acrylic resin processed by microwave polymerization; Group II: Classico resin processed in water bath at 74°C for 9 h (control-group); Group III: QC-20 fast heat-curing acrylic resin processed in boiling water for 20 min; Group IV: Onda-Cryl microwave acrylic resin processed at the same conditions of Group 1. Metallic referential pins were placed on the incisal border of the central incisors, buccal cusp of the first premolars, and the mesiobuccal cusp of the second molars. Transversal and anteroposterior distances were measured before and after the complete dentures processing with a linear optical microscope (Olympus Optical Co., Tokyo, Japan) accurate to 0.0005 mm. Data were subjected to ANOVA and Tukey's test at 5% significance levels. Results: Inside each group, dentures showed some tooth movement but without statistical difference before and after the polymerization. Conclusions: Dentures processed by microwave energy presented similar performance to those subjected to conventional cycles in water bath for most of distances evaluated.